Effectiveness and Safety of Preoperative Halo Gravity Traction-Assisted Posterior Spinal Fusion Surgery for Severe and Rigid Scoliosis: A Comparative Matched-Cohort Study - Yangpu Zhang; Bo Han; Jianqiang Wang; Yuzeng Liu; Yiqi Zhang; Yong Hai; Lijin Zhou (International Journal of Clinical Practice)
Background. Severe and rigid scoliosis poses significant challenges in surgical correction, and innovative approaches are continually sought to enhance effectiveness and ensure patient safety. Halo-gravity traction (HGT) continues to be a vital tool in managing severe spinal conditions, offering a nonsurgical or preoperative approach to address spinal deformities. However, the correction effect that HGT can achieve for severe and rigid spinal deformity is currently unclear and the impact of HGT on the selection of spinal osteotomy grade was still unknown. Methods. A retrospective matched-cohort study was conducted and a total of 74 patients from January 2018 to December 2021 in our institution were finally enrolled in this study, including 27 patients in the HGT group and 47 patients in the non-HGT group based on whether patients receive HGT or not. Comprehensive assessments including radiographic outcomes, surgical parameters, and clinical complications were collect and analyzed before and after correction surgery. Results. Of the patients included in the HGT group, 21 had thoracic curvature and 6 had thoracolumbar/lumbar curvature, compared with 38 and 9 in the non-HGT group, respectively (P=0.66). There was no significant difference in the etiologies of scoliosis between two groups (15/7/3/2 vs. 25/16/4/2, P=0.85). The main curve in HGT and non-HGT groups were corrected from an average of 113.69°–51.25° and 111.94°–63.79° (P<0.01). For the HGT group, the mean correction rate of focal kyphosis (FK) was 45.43%, which was significantly higher than those in the non-HGT group (33.98%, P<0.05). There were no statistically significant differences in preoperative parameters of sagittal vertical axis (SVA) (P=0.13) or thoracic kyphosis (TK) (P=0.07) between the two groups. Postoperatively, the HGT group showed significantly lower values in SVA (P=0.001) and TK (P=0.001) compared to the non-HGT group. However, there was no significant difference in the imaging parameters coronal vertical axis (CVA) and apical vertebral translation (AVT) between the two groups (P>0.05). In the preoperative surgical planning phase before HGT treatment, 26 patients were initially considered candidates for 3-column osteotomy (3CO), while one patient was evaluated as suitable for posterior column osteotomy (PCO). Following HGT treatment, the assessment changed with 11 patients identified as candidates for 3CO and 16 patients deemed suitable for PCO. The application proportion of 3CO was significantly higher in the non-HGT group than in the HGT group (P<0.05). The mean blood loss of the non-HGT group was significantly greater than that of the HGT group (666.67 ± 486.55 ml vs. 1024.47 ± 718.46 ml, P<0.05), but the surgical time showed no difference between the two groups (297.33 ± 66.89 mins vs. 299.15 ± 56.73 mins, P=0.90). The incidence of complications in the HGT group was 7.4%, which was significantly lower than that of the non-HGT group (P<0.05). Conclusion. This study showed that the use of HGT, as a feasible and safe strategy, has superior efficacy and safety for treating severe and rigid scoliosis and can reduce the level of osteotomy used during surgery to some extent.